METHODS FOR ANALYZING THE READINESS OF FUTURE MATHEMATICS TEACHERS TO INTEGRATE INTO THE DIGITAL EDUCATIONAL PROCESS - Sabyrkhanova П.; Ashirbayev Н.; Myrzabekov Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article is devoted to the study of the level of preparation of students of higher educational institutions for the use of innovative digital solutions when studying the course of mathematical analysis, in particular, differential and integral calculus of a function. The work assessed the level of preliminary knowledge of 4th year students (M.Auezov South Kazakhstan University, O.Zhanibekov South Kazakhstan State Pedagogical University), as well as their approach to new innovative teaching methods through an independent survey conducted through Google Forms. The authors analyze the data obtained, highlighting the main trends and problems associated with digital decision-making in the learning process. Special attention is paid to the presentation of an example of a problem reflecting the practical application of innovative approaches in teaching mathematical analysis. The results of the study allow us to determine the actions necessary for successful adaptation and integration into the process of studying mathematical analysis, innovative digital solutions and teaching methods. In conclusion, the article offers suggestions for improving educational programs for the training of future mathematics teachers, taking into account the development of their digital competence to ensure the successful integration of innovative technologies into the educational process.